Pulsed electromagnetic therapy in cancer treatment: Progress and outlook. Issue 5 (27th September 2022) - Xu, Wenjun; Xie, Xinjun; Wu, Hanyang; Wang, Xiaolin; Cai, Jiancheng; Xu, Zisheng; E, Shiju
Abstract: Cancer is one of the major diseases that endanger human health. Current treatment options have low patient tolerance, poor prognosis, and strong side effects. Pulsed electromagnetic therapy can selectively kill cancer cells by taking advantage of their own electromagnetic sensitivity specificity. Pulsed electric fields (PEFs), pulsed electromagnetic fields (PEMFs), and cold atmospheric plasma (CAP) are three main means that have promising application in cancer therapy. Pulsed electromagnetic therapy showed significant anticancer ability in vitro and in vivo. In this paper, we summarize the basic principles, methods, and state of art research of PEFs, PEMFs, and PEMFs for cancer therapy. Based on cancer pro‐oxidation therapy, we propose a combination therapy of electromagnetic field‐enhanced CAP for cancer therapy. Abstract : This paper summarizes the basic principles, methods and state of art research of PEFs, PEMFs, and PEMFs for cancer therapy. Based on cancer pro‐oxidation therapy, a combination therapy of electromagnetic field‐enhanced cold atmospheric plasma for cancer therapy is described in detail.